PENGEMBANGAN SMART E-MODUL BERBASIS GAMIFIKASI PADA PEMBELAJARAN IPA KELAS VIII SMP NEGERI 2 BONTORAMBA - Kartika; Andromeda Valentino Sinaga; Merrisa Monoarfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science instruction at Bontoramba State Junior High School 2 is still dominated by lecture-based methods and the use of textbooks, causing students to struggle to understand the material and remain underengaged in the learning process. This study aims to identify students’ needs, design and develop, and test the feasibility of a gamification-based smart e-module as an interactive learning medium for the 8th-grade science curriculum at Bontoramba State Junior High School 2. This study used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of three validators—a content expert, an instructional expert, and a media expert—as well as 30 eighth-grade students and a teacher. Data collection techniques included observation, interviews, and questionnaires. The results showed that the needs analysis achieved a percentage of 76.7% in the “needed” category. The content expert validation results achieved a 98% score, categorized as “highly valid”; the instructional expert validation results achieved a 90% score, categorized as “highly valid”; and the media expert validation results achieved a 90% score, categorized as “valid.” The results of the practicality test on a small group yielded a percentage of 94%, a large group 95%, and teacher responses 96%, all of which fell into the “highly practical” category. Thus, the gamification-based smart e-module was deemed valid and highly practical, making it suitable for use as an interactive learning medium for the science subject in eighth grade at SMP Negeri 2 Bontoramba.